Evolutionary Psychiatry and Nosology: Prospects and Limitations - Luc Faucher (Baltic International Yearbook of Cognition, Logic and Communication, 2012)
In this paper, I explain why evolutionary psychiatry is not where the next revolution in psychiatry will come from. I will proceed as follows. Firstly, I will review some of the problems commonly attributed to current nosologies, more specifically to the DSM. One of these problems is the lack of a clear and consensual definition of mental disorder; I will then examine specific attempts to spell out such a definition that use the evolutionary framework. One definition that deserves particular attention (for a number of reasons that I will mention later), is one put forward by Jerome Wakefield. Despite my sympathy for his position, I must indicate a few reasons why I think his attempt might not be able to resolve the problems related to current nosologies. I suggest that it might be wiser for an evolutionary psychiatrist to adopt the more integrative framework of “treatable conditions” (Cosmides and Tooby, 1999). As it is thought that an evolutionary approach can contribute to transforming the way we look at mental disorders, I will provide the reader with a brief sketch of the basic tenets of evolutionary psychology. The picture of the architecture of the human mind that emerges from evolutionary psychology is thought by some to be the crucial backdrop to identifying specific mental disorders and distinguishing them from normal conditions. I will also provide two examples of how evolutionary thinking is supposed to change our thinking about some disorders. Using the case of depression, I will then show what kind of problems evolutionary explanations of particular psychopathologies encounter. In conclusion, I will evaluate where evolutionary thinking leaves us in regard to what I identify as the main problems of our current nosologies. I’ll then argue that the prospects of evolutionary psychiatry are not good.